The S.C.C.O.R.E Model Approach to Academic Fraud Using Artificial Intelligence with Religiosity as a Moderating Variable - Cheery Asasi; Sriwidharmanely Sriwidharmanely (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2025)
This study examines the influence of the S.C.C.O.R.Es. Model elements (Stimulus, Capability, Collusion, Opportunity, Rationalisation, and Ego) on academic fraud, using Artificial Intelligence (AI), with religiosity as a moderating variable. The sample consisted of 410 accounting students who had previously used AI, selected through simple random sampling. Data were collected via an online Google Form and analysed using the SEM-PLS method with SmartPLS 4 software. The results show that five of the six S.C.C.O.R.E elements (Stimulus, Collusion, Opportunity, Rationalisation, and Ego) positively influence academic fraud using AI. However, capability does not show a significant effect. Religiosity has a significant negative direct effect on academic fraud but does not significantly moderate the relationship between the variables overall, except for stimulus and ego, where it shows a significant moderating effect. Based on the findings, higher education institutions, particularly accounting programs, can utilise these findings as a foundation to enhance their ethics curriculum by incorporating topics related to the ethical use of technology and AI in learning processes, and incorporating religious education into the curriculum as a strategy to strengthen students' self-control and prevent fraudulent behaviour.